2017
DOI: 10.17113/ftb.56.02.18.5474
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-Toothed and Dalmatian Sage Extracts on Platelet Aggregation

Abstract: SummarySage (Salvia) is genus of native Mediterranean plant used for aromatization of foods. In this study total polyphenol profile, antioxidant properties and antiplatelet effect of short-toothed sage (Salvia brachyodon Vandas) are analyzed and compared to most commonly used Salvia species (S. www.ftb.com.hrPlease note that this is an unedited version of the manuscript that has been accepted for publication. This version will undergo copyediting and typesetting before its final form for publication. We are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, a recent study has reported that the antiinflammatory effect on COX-2 gene suppression could be attributed to the extracts of the coffee leaves, which contain CGA, CF, mangiferin, rutin, and other bioactive molecules [57]. Synergistically inhibitory effect of agonists-induced platelet aggregation, which is related to antioxidant activity and reported in extracts of plants (such as Salvia species), is possibly caused by the interaction of persisting phenolic compounds [58][59][60]. Taken together, our findings suggest the potential inhibition of platelet aggregation and COXs activities in the following order: Drip coffee > espresso coffee > boiled coffee > instant coffee > CF, CGA, suggesting that the degree of inhibition may not be influenced by the anti-oxidative compounds and caffeine present in the coffee extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has reported that the antiinflammatory effect on COX-2 gene suppression could be attributed to the extracts of the coffee leaves, which contain CGA, CF, mangiferin, rutin, and other bioactive molecules [57]. Synergistically inhibitory effect of agonists-induced platelet aggregation, which is related to antioxidant activity and reported in extracts of plants (such as Salvia species), is possibly caused by the interaction of persisting phenolic compounds [58][59][60]. Taken together, our findings suggest the potential inhibition of platelet aggregation and COXs activities in the following order: Drip coffee > espresso coffee > boiled coffee > instant coffee > CF, CGA, suggesting that the degree of inhibition may not be influenced by the anti-oxidative compounds and caffeine present in the coffee extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Salvia officinalis L. and Salvia brachyodon Vand. leaves extracts showed antiplatelet activity in concentrations of 21 nmol L -1 (40). Analysis of constituents did not show relation with neither flavonoid nor polyphenolic acids content.…”
Section: Mechanisms Of Antiplatelet Action Of Individual Flavonoids Hmentioning
confidence: 73%
“…Furthermore, a recent study has reported that the anti-inflammatory effect on COX-2 gene suppression could be attributed to the extracts of the coffee leaves, which contain CGA, CF, mangiferin, rutin and other bioactive molecules [57]. Synergistically inhibitory effect of agonists-induced platelet aggregation, which is related to antioxidant activity and reported in extracts of plants (such as Salvia species), is possibly caused by the interaction of persisting phenolic compounds [58][59][60]. Taken together, our findings suggest the potential inhibition of platelet aggregation and COXs activities in the following order; drip coffee > espresso coffee > boiled coffee > instant coffee > CF, CGA, suggesting that the degree of inhibition may not be influenced by the anti-oxidative compounds and caffeine present in the coffee extracts.…”
Section: Discussionmentioning
confidence: 99%